2018
DOI: 10.1088/1748-9326/aac4bb
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration simulations in ISIMIP2a—Evaluation of spatio-temporal characteristics with a comprehensive ensemble of independent datasets

Abstract: Actual land evapotranspiration (ET) is a key component of the global hydrological cycle and an essential variable determining the evolution of hydrological extreme events under different © 2018 The Author(s). Published by IOP Publishing LtdEnviron. Res. Lett. 13 (2018) 075001 climate change scenarios. However, recently available ET products show persistent uncertainties that are impeding a precise attribution of human-induced climate change. Here, we aim at comparing a range of independent global monthly la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 105 publications
2
43
0
Order By: Relevance
“…The underestimation of runoff by certain models, particularly in the NDR hydrobelt, may be a result of excessive evapotranspiration (as reported for MATSIRO by [19]). Moreover, the simulation of evapotranspiration has been shown to vary widely between the ISIMIP2a global-scale hydrological models [63]. Several models struggle to accurately simulate the timing and magnitude of long-term MMR in all months of the year in NDR and the first and/or last months in other hydrobelts.…”
Section: Models' Performance Across Hydrobeltsmentioning
confidence: 99%
“…The underestimation of runoff by certain models, particularly in the NDR hydrobelt, may be a result of excessive evapotranspiration (as reported for MATSIRO by [19]). Moreover, the simulation of evapotranspiration has been shown to vary widely between the ISIMIP2a global-scale hydrological models [63]. Several models struggle to accurately simulate the timing and magnitude of long-term MMR in all months of the year in NDR and the first and/or last months in other hydrobelts.…”
Section: Models' Performance Across Hydrobeltsmentioning
confidence: 99%
“…ET simulation in LSMs is regulated by multiple biophysical and physiological properties or processes, including but not limited to stomatal conductance, leaf area, root water uptake, soil water, runoff and sometimes nutrient uptake (Famiglietti and Wood, 1991;Huang et al, 2016;Lawrence et al, 2007). Although almost all current LSMs have these components, different parameterization schemes result in substantial differences in ET estimation (Wartenburger et al, 2018). Therefore, in recent years, the multi-model ensemble approach has become popular in improving the accuracy of global terrestrial ET estimation (Mueller et al, 2011;Wartenburger et al, 2018).…”
Section: Process-based Land Surface Models (Lsms)mentioning
confidence: 99%
“…Knowledge of the uncertainties in global terrestrial ET estimates from different approaches is the prerequisite for future projection and many other applications. In recent years, several studies have compared multiple terrestrial ET estimates (Khan et al, 2018;Mueller et al, 2013;Wartenburger et al, 2018;Zhang et al, 2016b). However, most of these studies just analyzed multiple datasets of the same approach or focused on investigating similarities and differences among different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Müller Schmied et al () showed that by taking into account uncertainties of climate and land cover data, global discharge was changed by 5% whereas actual evapotranspiration was unaffected. In a number of studies, the performance of the WGHM in the simulation of discharge, reservoir, radiation, and evapotranspiration was evaluated, and it was found that the model estimate in the gridded and basin scales generally outperforms other global models (Masaki et al, ; Müller Schmied et al, 2016b; Veldkamp et al, ; Wartenburger et al, ; Zaherpour et al, , ; Zhao et al, ). The comparison of seasonal amplitudes of the model to GRACE data showed that WGHM underestimates TWSA in the Southern Hemisphere and the tropics but compares favourably with GRACE in the Northern Hemisphere (Scanlon et al, ).…”
Section: Discussionmentioning
confidence: 99%